The study of surface roughness on laminated transfemoral socket / Nik Abdul Muiz Nik Zainuddin - Nik Abdul Muiz , Nik Zainuddin (2023)
Prosthesis is an artificial limb used by a patient with amputation to replace the original limb. Common material used in Malaysia in fabricating a transfemoral sockets is the polypropylene plastics instead of laminated composite. Polypropylene is known to be weaker and less durable compared to laminated composite. However, discussion of other mechanical characteristics such as surface profile which can contribute to patient’s comfort is still very limited. Thus, this research aims to study the surface analysis in laminated transfemoral socket fabricated using different reinforcement materials, type of resin and resin to hardener ratio. In this study, 15 transfemoral sockets were fabricated with different reinforcement materials and different types of resin and ratio. The lateral part of the socket was then cut as a sample for surface testing. A total of 20 trials were done on each surface sample using the Mitutoyo Surftest SJ-210 and the data was recorded in Microsoft Excel. An analysis was done to evaluate the internal surface of the sockets after the samples were tested using the Mitutoyo SurfTest SJ-210 series. Transfemoral socket interface directly to the patient skin without any usage of liner which could lead to skin impairment and inflammation. Fibreglass was shown to be the smoothest surface as the average surface roughness is the lowest at 2.318 μm, followed by Polyester at 2.380 μm, Perlon at 2.682 μm, Elastic Stockinette at 2.722 μm and Dacron felt at 3.750 μm. As for the different types of resin and hardener, the smoothest internal surface was produced by the 3:2 epoxy resin to hardener ratio, followed by 3:1, 2:1 and lastly with value higher than 1, 2:3. The socket made with 1:3 resin to hardener ratio was excluded in surface testing as the composite did not cure and ended up in a liquid state. As for the acrylic resin, the smoothest surface was produced by the ratio of 100:1 resin to hardener, with Ra value of 1.0086 μm. The 100:1 resin to hardener ratio took the longest time to cure at 167 minutes, thus it is expected to produce the smoothest surface. Meanwhile, the cure time for 100:2 resin to hardener ratio was reduced significantly to just 43 minutes, and this also doubled the Ra value to 2.3622 μm as compare to 100:1 ratio. This result suggested that laminated socket using epoxy resin reinforced with fibreglass produces the smoothest socket compare to acrylic and other reinforcement materials.